Dicarboxylate transport by rhizobia - Yurgel, Svetlana N.; Kahn, Michael L. (FEMS microbiology reviews, 2004)
Soil bacteria collectively known as rhizobia are able to convert atmospheric dinitrogen to ammonia while participating in a symbiotic association with legume plants. This capability has made the bacteria an attractive research subject at many levels of investigation, especially since physiological and metabolic specialization are central to this ecological niche. Dicarboxylate transport plays an important role in the operation of an effective, nitrogen-fixing symbiosis and considerable evidence suggests that dicarboxylates are a major energy and carbon source for the nitrogen-fixing rhizobia. The dicarboxylate transport (Dct) system responsible for importing these compounds generally consists of a dicarboxylate carrier protein, DctA, and a two component kinase regulatory system, DctB/DctD. DctA and DctB/D differ in the substrates that they recognize and a model for substrate recognition by DctA and DctB is discussed. In some rhizobia, DctA expression can be induced during symbiosis in the absence of DctB/DctD by an alternative, uncharacterized, mechanism. The DctA protein belongs to a subgroup of the glutamate transporter family now thought to have an unusual structure that combines aspects of permeases and ion channels. While the structure of C 4-dicarboxylate transporters has not been analyzed in detail, mutagenesis of S. meliloti DctA has produced results consistent with the alignment of the rhizobial protein with the more characterized bacterial and eukaryotic glutamate transporters in this family.